Pengaruh Masa Kerja, Usia, Pangkat dan Golongan Terhadap Motivasi Kerja Pegawai Negeri Sipil Pada Kantor SAR Pontianak - Devi Yasmin; Mimin Suherman (JURNAL MANAJEMEN MOTIVASI, 2015)
This study discusses the effect of length of service, age, rank and groups to work motivation of civil officers in Pontianak SAR office. The study was correlational, the data obtained through interviews, observations, and questionnaires, and secondary data. The population is all employees in the office and SAR Pontianak using saturated sample. Using the chi-square analysis. Research results revealed that there was an effect on the motivation of working time civil servants SAR Office of Pontianak, because Chi Square Count 4.90> 0.0075 Chi Square Table. There is an effect of age on the Civil Service Office motivation SAR Pontianak, because Chi Square Count 0.23> Chi Square Table 0.16. No influence Rank and type of motivation SAR Office of the Civil Service Pontianak, because Chi Square Count 13.02 <Chi Square Table 15.53.